(3GdbhGYO hGdebGUOs - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s
(3ChdgG (B:s
(3gPG GHJOG TQhYfG ai Gdaf GdKGdK GdPi gh CLd eG ai gPG GdcJGH s
(3BNQgG (B:s
(3hgPg gi GdWQjbI GdJi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B227 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B303s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(122) s
(3JHUQI GdJQGLe(Bs
(3JQLeI GdeDda (B:s
Keywords: (3GdadSaI hGdefWbs